The Need for Orthodontic Treatment among Vietnamese School Children and Young Adults - Nguyen, Son Minh (Hindawi Publishing Corporation, 2014)
Objective. The aim of this study was to evaluate the need for orthodontic treatment among 12-year-old school children and 18-year-olds from Da Nang, Vietnam. Basic Research Design. A random representative sample of 200 12-year-old children from primary schools in Da Nang city was gathered. In addition, 200 18-year-old students were randomly selected from among the 4000 students studying at Da Nang University of Medical Technology and Pharmacy, Vietnam. All the subjects were evaluated according to Angle's molar relationship, the presence of malocclusion, and the components of the Index of Orthodontic Treatment Need (Dental Health Component, DHC, and Aesthetic Component, AC). Results. The DHC of index of orthodontic treatment need (IOTN) for 12-year-olds was in 60% of cases no or little, in 21% of cases moderate, and in 19% of cases definitive, while the prevalence of moderate and definitive need for treatment among the 18-year-olds was 24% and 30.5%, respectively. The prevalence of class III malocclusion, contact point displacement, and crossbite was higher in 18-year-olds than among the 12-year-olds, while the prevalence of increased overjet and increased overbite had decreased in 18-year-olds compared to the group of 12-year-olds. Conclusions. There is a strong need for orthodontic treatment in Vietnam's population. The need for orthodontic treatment was determined by contact point displacement, crossbite, increased overjet, and increased overbite.